(untitled) (Al-Mansour Journal, 2026)
This research aims to study the factors affecting the quality of accounting earnings during economic crises, focusing on the impact of internal factors such as corporate governance and the quality of internal controls, and external factors such as the economic environment, legislation, and the quality of external audits, in addition to company characteristics (size, indebtedness, and sector). The research adopted a descriptive-analytical-causal approach using secondary financial data, audit reports, and questionnaires administered to financial management and accountants. The results showed a significant impact of both internal and external factors on the quality of accounting earnings. The study indicates the necessity of strengthening internal controls and effective governance, and implementing rigorous external audit mechanisms to maintain the credibility of financial statements.